Dose-Related Association Between Urinary Cotinine-Verified Smoking Status and Dyslipidemia among Korean Men: The 2008–2010 Korea National Health and Nutrition Examination Survey. (19th September 2014) - Nam, Ga Eun; Kim, Do Hoon; Park, Yong Gyu; Han, Kyungdo; Choi, Youn Seon; Kim, Seon Mee; Ko, Byung Joon; Kim, Yang Hyun; Lee, Kyung Shik; Baek, Sung Joon
<x xml:space="preserve">Abstract</x> This cross-sectionally designed study was based on data collected during the 2008–2010 Korea National Health and Nutrition Examination Survey. A total 3231 South Korean men aged more than 19 years were included. Urinary cotinine concentrations were measured. Smoking status was defined using questionnaire responses and urinary cotinine concentrations. Hierarchical multivariate logistic regression analyses were used to assess the association of urinary cotinine concentrations with the prevalence of dyslipidemia and various parameters of dyslipidemia. There is a significant dose-related association between smoking as assessed by urinary cotinine concentration and dyslipidemia and various parameters of dyslipidemia among South Korean men.